EFFECT OF INTERPERSONAL COMUNICATION, REWARD, AND PUNISHMENT ON PERFORMANCE OF EMPLOYEES - Fatmasari Fatmasari; Nurdiana Nurdiana (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
This study aims to analyze (1) the influence of interpersonal communication on the performance of millennial employees, (2) the effect of rewards on the performance of millennial employees, (3) the effect of punishment on the performance of millennial employees, and (4) the influence of interpersonal communication, reward, and punishment on the performance of millennial employees. The research was conducted at the BPRS Niaga Madani Office for 2 (two) months, from March to April 2022. The population used in this study were all 32 millennial employees of the BPRS Niaga Madani Office. Due to the relatively small number of samples (less than 100 people) and easily accessible by researchers, a saturated sample was determined. The results of the study conclude that (1) interpersonal communication has no significant effect on the performance of millennial employees, (2) rewards have no significant effect on the performance of millennial employees, (3) punishment has a positive and significant effect on the performance of millennial employees, and (4) interpersonal communication, reward, and punishment have an effect on positive and significant impact on the performance of the millennial employees of the BPRS Niaga Madani Office.